Contoh Penerapan Penetapan Zona Ekonomi Eksklusif (Studi Kasus Imajiner Amalea v. Ritania atas Malachi Gap) - Munir, Misbachul; Elsyam, Churun Ain Nabila; Musyarri, Fazal Akmal; Sihotang, Nenny; Afriyanti, Puput Brenda; Siregar, Zipora Nadya A. (CV Rewang Rencang, 2020)
The Law of the Sea divides the maritime territorial boundary of a country into several parts, one of which is the Exclusive Economic Zone or which is often referred to as EEZ. The Exclusive Economic Zone is a zone with a maximum distance of 200 miles in which resources can be utilized but cannot be controlled by a country due to purposes such as shipping and aviation navigation which are generally required. However, due to the nature of its free use, it can lead to conflicts between countries because this is like dominoes that have a correlation with one another. In this paper, it will be described in relation to examples of implementing EEZ conflict resolution in imaginary cases or fictional cases of the State of Amalea and the State of Ritania as a simulation of the settlement of the EEZ determination based on the UNCLOS 1982 sea law. This simulation has fictional factual dynamics that are interesting from a legal perspective with a settlement that is conventional namely the consensus of the parties. Referring to the 1982 UNCLOS, the use of marine aspects needs to be considered so as not to disturb other countries.